ANALISIS PARETO 80/20 UNTUK PENGENDALIAN BIAYA PEKERJAAN ARSITEKTUR HOTEL BERTINGKAT TINGGI - Nadiifa Firsty; Yani Rahmawati (Jurnal Arsitektur ARCADE, 2026)
Abstract: Hotel construction projects are highly complex, involving numerous categories of architectural work that make it difficult to prioritize the budget. Without a systematic approach, project managers risk allocating resources to items with little impact. This study applies the Pareto 80/20 principle to analyze the distribution of architectural work costs in the construction of the Voyou Bengawan Surakarta Hotel, a 14-story hotel on Jalan Ir. Sutami, Surakarta City, Central Java. The primary data is sourced from the Bill of Quantities (BoQ) for all architectural work from the basement to the 14th floor, with a total value of Rp23,413,906,489 divided into seven categories. The method used is descriptive quantitative analysis involving Pareto ranking, percentage calculations, and cumulative analysis using Microsoft Excel. The results identify four categories as the "Vital Few", namely facade and canopy work (32.68%), wall work (32.40%), door and window frames (12.85%), and flooring (10.51%), cumulatively accounting for 88.44% of the total BoQ value. The remaining three categories, ceiling work (5.16%), painting (3.90%), and miscellaneous work (2.50%), are classified as "Trivial Many". These findings demonstrate that Pareto analysis is a practical framework for directing procurement strategies, budget monitoring, and on-site supervision toward the most economically significant categories of architectural work. Keywords: Pareto Analysis, Bill of Quantities, Cost Control, Architectural Work Abstrak: Proyek konstruksi hotel memiliki kompleksitas tinggi dengan banyak kategori pekerjaan arsitektur yang menyulitkan penetapan prioritas anggaran. Tanpa pendekatan sistematis, manajer proyek berisiko mengalokasikan sumber daya pada item yang kurang berdampak. Penelitian ini menerapkan prinsip Pareto 80/20 untuk menganalisis distribusi biaya pekerjaan arsitektur pada pembangunan Hotel Voyou Bengawan Surakarta, hotel 14 lantai di Jalan Ir. Sutami, Kota Surakarta, Jawa Tengah. Data utama bersumber dari Bill of Quantities (BoQ) seluruh pekerjaan arsitektur mulai lantai basement hingga lantai ke-14, dengan total nilai Rp23.413.906.489 yang terbagi dalam tujuh kategori. Metode yang digunakan adalah kuantitatif deskriptif dengan perangkingan Pareto, perhitungan persentase, dan analisis kumulatif menggunakan Microsoft Excel. Hasil penelitian mengidentifikasi empat kategori sebagai "Vital Few", yaitu pekerjaan fasad dan kanopi (32,68%), dinding (32,40%), kusen pintu dan jendela (12,85%), serta lantai (10,51%), yang secara kumulatif mencakup 88,44% dari total nilai BoQ. Tiga kategori lainnya, yaitu plafond (5,16%), pengecatan (3,90%), dan pekerjaan lain-lain (2,50%), diklasifikasikan sebagai "Trivial Many". Temuan ini membuktikan bahwa analisis Pareto merupakan kerangka kerja yang praktis untuk mengarahkan strategi pengadaan, pemantauan anggaran, dan pengawasan lapangan pada kategori pekerjaan arsitektur yang paling signifikan secara ekonomi. Kata Kunci: Analisis Pareto, Bill of Quantities, Pengendalian Biaya, Pekerjaan Arsitektur